Can attention allocation affect firm's environmental innovation: the moderating role of past performance. Issue 9 (2nd September 2022) - Liao, Zhongju; Lu, Jie; Yu, Yubing; Zhang, Zuopeng (Justin)
ABSTRACT: Based on the upper echelons theory and the attention-based view of the firm, this study constructed a relationship model between the top management team's attention allocation and the firm's environmental innovation. Given the firm's environmental innovation activities may be influenced by resource factors, we selected the past performance of the firm (measured by profit) as the moderating variable. Three hundred and twelve listed Chinese companies were selected as the research sample, and NVivo11 and SPSS21.0 software were used to analyze the relationships among attention allocation, past performance, and environmental innovation. The results showed that the more attention that the top management team allocated to policies and consumers, the more likely the firm was to adopt an environmental innovation strategy; however, the more attention that top management team allocated to competitors and employees, the less likely it was the firm adopted an environmental innovation strategy. Besides, the past performance of the firm played a positive moderating role between the top management team's attention to consumers and the environmental innovation of the firm.